Development of a GIS based screening tool for evaluating stormwater harvesting sites in urban areas - Inamdar, P.; Cook, Simon; Sharma, A.; Corby, N.; O'Connor, J.; Perera, B. (2011)
The recent drought in Australia, together with concerns about climate change and growing urban demand for water have highlighted the need of managing water resources in a more sustainable way. Water supply restrictions have been used by respective State Governments in major Australian cities to cope up with dwindling water resources. Since the last decade, alternative, non-traditional water resources have been seen as an increasingly attractive means to supply non-potable urban water demands. Among several alternative water resources, stormwater harvesting and reuse has emerged as a viable form of sustainable water management, as it not only offers a potential alternative water supply for non-drinking water uses and thus improving the security of water supply, but also provides a means to reduce stormwater pollution in waterways. In the urban context, the selection of suitable stormwater harvesting sites is of prime importance for water managers, and must be established in order to develop the detailed engineering designs. In this regard, Geographic Information Systems (GIS) can be utilized as effective tools to analyze various spatial datasets. The current literature focuses on applying GIS to identifying suitable stormwater harvesting locations in rural catchments. However, the application of GIS has been very limited in existing urban areas for identifying suitable sites for stormwater harvesting. To address this knowledge gap, the present research was focused on developing a GIS screening tool for identifying potential stormwater harvesting locations in existing urban areas, using pre defined suitability criteria. The methodology was then applied to an existing urban area to identify suitable stormwater harvesting sites. A portion of the Melbourne City Council (MCC) within the service area of water retailer, City West Water (CWW) was considered as the case study. CWW is one of the three retail water companies in the Melbourne metropolitan area, Australia, providing water, sewage, trade waste and recycled water services to its residential and non-residential customers. The key criteria considered for developing the screening tool were urban runoff and water demand. These criteria were evaluated with respect to 'accumulated catchments', which was a concept introduced in this study. The accumulated catchments referred to here were the aggregated upstream catchments increasing in drainage area from upstream to downstream of the catchment. Spatial maps were generated for each of these criteria. This procedure involved extensive data collection from CWW, different Australian Government authorities and research institutions. The rational method was used to estimate potential runoff, which involved integration of a pervious-impervious area map, a runoff coefficient map and an interpolated rainfall map. The runoff analysis was done using the annual average values of rainfall for the drought period of 1997-2009. Water demands considered included irrigation demands from parks, ovals, and council reserves, which were represented in GIS as demand volume per park landuse area. Demand analysis was undertaken using water consumption values of the parks for year of 2010. Annual scale chosen was deemed suitable for this preliminary screening process. The accumulated catchment layer was generated from the Digital Elevation Model (DEM) of 10m. The runoff and demand layers were overlayed with accumulated catchments to obtain the ratios of available runoff to required demands from each of the accumulated catchments. The drainage outlets of the accumulated catchments were thought as potential stormwater harvesting sites. Thus, sites with high ratios of supply to demand indicated the high suitability of a given accumulated catchment for stormwater harvesting. The drainage outlets of high ratio catchments were selected, ranked and termed as suitable stormwater harvesting sites. Thus, the GIS screening tool methodology has provided a rational approach in identifying potential sites for stormwater harvesting in existing urban areas, which will aid water authorities such as CWW in their infrastructure planning and decision making. Once the suitable sites are identified from the GIS based screening tool, detail conceptual designs will be developed for these identified sites. These sites will be evaluated the with respect to social, environmental and economic criteria to select the most suitable sites and designs, as part of future research.